Tindakan Sosial Masyarakat Dalam Pemenuhan Air Bersih Pada Daerah Kekeringan di Dusun Tlogopule Kabupaten Tuban - Joko Mulyono; Dinda Margesta Priantika (Prodi Sosiologi FISIP ULM, 2023)
The limitations of water sources and continuous water services are the problems of water crises that occur year after year in areas prone to drought. In the face of this condition, people take various actions to fulfill clean water used for daily necessities. The location of this study is in Tlogopule Hamlet, Prunggahan Kulon Village, Semanding District, Tuban Regency. This study used a qualitative descriptive approach, with data collection techniques through observation, interviews and documentation. The study used Max Weber's theory of Social Action, in which actions were performed based on specific reasons and goals to be achieved. In this study, we used three theories out of four proposed by Max Weber. Got that result; 1. The act of Instrumental Rationality is carried out by buying clean water, looking for water in wells, washing at neighboring village water sources and subscribing to water at neighboring village HIPPAM; 2. Value measures by performing the act of receiving clean water aid and water subscription fees with neighbors; 3. Traditional actions by making talang and jeding (waterproofing) to hold rainwater. The water crisis that continues to occur, especially during the dry season, has led the public to the understanding that drought is a common disaster. Drought has brought the community's customs of working together to survive and coexist with drought.